A guideline for school teachers on cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) - Nurumal, Mohd Said; Che Hasan, Muhammad Kamil; Jamaludin, Sumaiyah @ ThandarSoe; Aung, Khin Thandar; Mohd Nor, Mahirah; Mat Hussain, Maryam Farah Nadia (2021)
Globally, sudden cardiac arrests are the most common cause of death. The statistics from more than 190 countries showed that heart disease remains the number one global cause of death with 17.3 million deaths each year based on the Heart Disease and Stroke Statistics 2015 update. In Malaysia, coronary heart disease also remains the number one killer in terms of diseases and health-related problems for the last ten years, from 2005 to 2014. In 2015, the number of deaths resulted from coronary heart disease recorded the highest percentage in Malaysia with 13.7% including sudden cardiac arrest. Studies have shown that early CPR and Automated External Defibrillation (AED) are the only way to reverse a cardiac arrest. Thus, this booklet aimed to provide knowledge on how to perform the CPR and how to use the AED in OHCA by the bystanders